CASE STUDY: MISUSE OF COMMUNICATION TOOLS BY INMATES IN NARCOTICS TRAFFICKING IN PRISONS - Ghina Nur Afifah; Nur Abida Yasvin; Ilham Ilham (Ann Publisher, 2025)
Abstract: Background. Drug abuse in Indonesia has reached an alarming level, with drugs no longer being an illicit item that is difficult to get, but a straightforward item to get. This is due to the effects of opium and pleasure on the user's body, which often starts from trial and error, follows friends, and ends in addiction. Aims. This study aims to analyze the causes of the increase in narcotics trafficking, examine the involvement of social media in narcotics trafficking and transactions, understand the mechanism of efforts to counter narcotics crimes in Correctional Institutions, and the implications of legal sanctions for perpetrators of narcotics crimes. Methods. This research uses an empirical juridical approach. This approach focuses on analyzing the actual conditions that occur in society and collecting relevant information related to the problems researched through interviews. Result. Based on the findings of the study, it can be seen that narcotics abuse arises due to the influence of internal and external factors. In addition, the misuse of communication tools by inmates in the illicit circulation of narcotics has a negative impact, in the form of an increase in drug trafficking, the emergence of organized crime, and the difficulty of supervision by the Correctional Institution. Conclusion. With the research conducted by researchers, various mechanisms have been produced to overcome the abuse of communication tools by inmates in narcotics trafficking in correctional institutions, which include preventive, preemptive, repressive, and rehabilitation efforts. Implementation. The mechanism of efforts to overcome the misuse of communication devices by inmates in narcotics circulation in prisons can be carried out